Misleading Goldmann applanation tonometry in a post-LASIK eye with interface fluid syndrome - Senthil, Sirisha (Medknow Publications, 2010)
A 21-year-old myope presented with decreased vision and corneal edema following vitreoretinal surgery for retinal detachment. While intraocular pressure (IOP) measurement with Goldmann applanation tonometer (GAT) was low, the digital tonometry indicated raised pressures. An interface fluid syndrome (IFS) was suspected and confirmed by clinical exam and optical coherence tomography. A tonopen used to measure IOP through the peripheral cornea revealed elevated IOP which was the cause of the interface fluid. Treatment with IOP-lowering agents resulted in complete resolution of the interface fluid. This case is being reported to highlight the fact that IFS should be suspected when there is LASIK flap edema and IOP readings using GAT are low and that GAT is not an optimal method to measure IOP in this condition. Alternative methods like tonopen or Schiotz tonometry can be used.